Oligonucleotide Therapy for Obstructive and Restrictive Respiratory Diseases - Liao, Wupeng (Molecules, 2017)
Inhaled oligonucleotide is an emerging therapeutic modality for various common respiratory diseases, including obstructive airway diseases like asthma and chronic obstructive pulmonary disease (COPD) and restrictive airway diseases like idiopathic pulmonary fibrosis (IPF). The advantage of direct accessibility for oligonucleotide molecules to the lung target sites, bypassing systemic administration, makes this therapeutic approach promising with minimized potential systemic side effects. Asthma, COPD, and IPF are common chronic respiratory diseases, characterized by persistent airway inflammation and dysregulated tissue repair and remodeling, although each individual disease has its unique etiology. Corticosteroids have been widely prescribed for the treatment of asthma, COPD, and IPF. However, the effectiveness of corticosteroids as an anti-inflammatory drug is limited by steroid resistance in severe asthma, the majority of COPD cases, and pulmonary fibrosis. There is an urgent medical need to develop target-specific drugs for the treatment of these respiratory conditions. Oligonucleotide therapies, including antisense oligonucleotide (ASO), small interfering RNA (siRNA), and microRNA (miRNA) are now being evaluated both pre-clinically and clinically as potential therapeutics. The mechanisms of action of ASO and siRNA are highly target mRNA specific, ultimately leading to target protein knockdown. miRNA has both biomarker and therapeutic values, and its knockdown by a miRNA antagonist (antagomir) has a broader but potentially more non-specific biological outcome. This review will compile the current findings of oligonucleotide therapeutic targets, verified in various respiratory disease models and in clinical trials, and evaluate different chemical modification approaches to improve the stability and potency of oligonucleotides for the treatment of respiratory diseases.